Stakeholder Analysis on Community Forest Management Partnership and Independent - Dimas Alfred Pasetia; Hardjanto .; Yulius Hero (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Timber of community forest in one of the alternative supply that is needed by the wood processing industries. Partnership and independent of community forest can be realized in the relationship between farmers and industry. However, parts of the community forest system is represented by different stakeholders, which are interrelated in a system. This study analyzed stakeholder interest, influences and relationships between partnership and independent of community forest management. The study was conducted in Probolinggo District and respondents were selected using snowball sampling. There were 15 stakeholders identified as being involved in the partnership of community forest management of which were classified 4 as key players, 2 as context setters, 5 as subjects and 5 as crowds. There were 12 stakeholders identified as being involved in the independent of community forest management of which were classified 3 as key players, 1 as context setters, 5 as subjects and 3 as crowd. The performances of each stakeholder can be controlled if the integration of relationships and rules has been established. Keywords: community forest, independent, partnership, stakeholders